Gene Delivery to Nonhuman Primate Preimplantation Embryos Using Recombinant Adeno‐Associated Virus. Issue 21 (4th September 2019) - Wang, Dan; Niu, Yuyu; Ren, Lingzhi; Kang, Yu; Tai, Phillip W. L.; Si, Chenyang; Mendonca, Craig A.; Ma, Hong; Gao, Guangping; Ji, Weizhi
Abstract: Delivery of genome editing tools to mammalian zygotes has revolutionized animal modeling. However, the mechanical delivery method to introduce genes and proteins to zygotes remains a challenge for some animal species that are important in biomedical research. Here, an approach to achieve gene delivery and genome editing in nonhuman primate embryos is presented by infecting zygotes with recombinant adeno‐associated viruses (rAAVs). Together with previous reports from the authors of this paper and others, this approach is potentially applicable to a broad range of mammals. In addition to genome editing and animal modeling, this rAAV‐based method can facilitate gene function studies in early‐stage embryos. Abstract : Delivery of genome editing tools to mammalian zygotes has revolutionized animal modeling. However, the mechanical delivery method to introduce genes and proteins to zygotes remains a challenge for some animal species that are important in biomedical research. A viral vector infection approach to achieve gene delivery and genome editing in nonhuman primate embryos is presented in this study.